2018
DOI: 10.1002/jcb.27182
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐RNAs as critical regulators of matrix metalloproteinases in cancer

Abstract: Metastasis is known to be one of the important factors associated with cancer-related deaths worldwide. Several cellular and molecular targets are involved in the metastasis process. Among these targets, matrix metalloproteinases (MMPs) play central roles in promoting cancer metastasis. MMPs could contribute toward tumor growth, angiogenesis, migration, and invasion via degradation of the extracellular matrix and activation of pre-pro-growth factors. Therefore, identification of various cellular and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 210 publications
(303 reference statements)
0
45
0
1
Order By: Relevance
“…43 MiRNAs is a class of noncoding RNAs that act as epigenetic modulators. [44][45][46][47][48][49][50][51] These molecules via affecting a wide range of cellular and molecular targets exert their regulatory effects. [52][53][54][55][56][57][58] It has been showed that deregulation of this molecules are associated with initiation and progression of various diseases and pathological conditions.…”
Section: Curcumin and Retinal Diseases Therapymentioning
confidence: 99%
“…43 MiRNAs is a class of noncoding RNAs that act as epigenetic modulators. [44][45][46][47][48][49][50][51] These molecules via affecting a wide range of cellular and molecular targets exert their regulatory effects. [52][53][54][55][56][57][58] It has been showed that deregulation of this molecules are associated with initiation and progression of various diseases and pathological conditions.…”
Section: Curcumin and Retinal Diseases Therapymentioning
confidence: 99%
“…MicroRNAs are small non‐coding RNAs which act as epigenetic regulators . These molecules play critical roles in regulation of gene expression in the RNA and protein levels .…”
Section: Microrna and Exosome‐based Vaccinementioning
confidence: 99%
“…96 9 | MICRORNA AND EXOSOME-BASED VACCINE MicroRNAs are small non-coding RNAs which act as epigenetic regulators. [99][100][101][102][103][104][105][106] These molecules play critical roles in regulation of gene expression in the RNA and protein levels. 22,[107][108][109][110][111][112][113] It has been shown that deregulation of microRNAs is associated with initiation and progression of various diseases such as infectious diseases, cardiovascular diseases, diabetes, neurogenerative diseases, and cancer.…”
Section: Influenza Rna Vaccinementioning
confidence: 99%
“…6 | MicroRNA AND PANCREATIC β CELLS: PHYSIOLOGICAL AND PATHOLOGICAL ASPECTS miRNAs are a group of noncoding RNAs which plays a crucial role in epigenetic procedures (Fathullahzadeh, Mirzaei, Honardoost, Sahebkar, & Salehi, 2016;Golabchi et al, 2018;Mashreghi et al, 2018;Mirzaei, Khataminfar, et al, 2016;Mirzaei, Naseri, et al, 2016;Mirzaei, Sahebkar, Jaafari, Goodarzi, & Mirzaei, 2017;Saadatpour et al, 2016;Salarinia et al, 2016). These structures exert their effects by means of affecting on some cellular and molecular pathways Jamali et al, 2018;Noruzi et al, 2018).…”
Section: Oxidative Stress and T2dmentioning
confidence: 99%